Effectiveness of the School Literacy Movement Program: An Impact Study Using the Kirkpatrick Model in Kuningan Regency - Simorangkir, Melda Rumia Rosmery; Deliviana, Evi (FKIP Universitas Lampung, 2025)
Effectiveness of the School Literacy Movement Program: An Impact Study Usiang the Kirkpatrick Model in Kuningan Regency. Objective: This study aims to evaluate the effectiveness of the School Literacy Movement program at the junior high school level in Kuningan Regency, West Java, in response to the province’s low literacy index (39.47% in 2019) and alarming literacy scores in the 2022 Education Report. The evaluation applies the Kirkpatrick Model across four levels: reaction, learning, behavioral change, and final outcomes. Method: The study employs a sequential exploratory mixed methods design. The initial phase involved qualitative data collection through interviews, observations, and document analysis to explore the implementation of School Literacy Movement and the contextual factors influencing its effectiveness. The qualitative findings informed the development of a quantitative instrument, which was distributed to students using purposive sampling in schools with active Guru Penggerak (Education Reform Teachers). Quantitative data were analyzed using path analysis to examine direct and indirect relationships among variables such as literacy comprehension, reading habits, social interaction, school climate, and character development. Integration of qualitative and quantitative data occurred during the interpretation phase to enhance the validity and depth of findings. Findings: The GLS program significantly improved students' literacy comprehension and reading habits. Teacher-student relationships (KHGdS) and peer interactions (HSASD) had a significant positive effect on character development (p = 0.007 and p < 0.001). However, experiences of bullying (FPp) negatively affected the school safety climate (KIKS), although they still influenced student character (p < 0.001). Conclusion: The GLS program is effective in enhancing literacy and character among students. However, creating a safe and supportive school environment remains a critical challenge. This study highlights the need to integrate literacy efforts with emotionally responsive policies, teacher capacity-building, and holistic approaches that prioritize student well-being. Keywords: program evaluation, school literacy movement, kirkpatrick, reading culture, student literacy.